OPTIMIZATION OF THE DIALOGICAL PATROL BY SAMAPTA UNITS IN THE PREVENTION OF BULGLAR AT TERITORY OF POLRES GROBOGAN JURISDICTION - AKBAR RAFSANJANI - (Indonesian Journal of Police Studies, 2022)
Bulglar (PENCURIAN DENGAN PEMBERATAN) often dominates in the records of social security disturbances cases in the territory of Polres Grobogan jurisdiction. Thus, the Polres Grobogan, through the Samapta Units, has a role in controlling and crime preventing by taking preventive measures in the form of the dialogical patrol. The implementation of dialogical patrol is quite efficient but not yet fully optimal. This can be seen from the thief index in this territory still fluctuating in its monthly period. This situation encourages researcher to deepen research with the topic of optimizing the Dialogical Patrol to prevent crimes with weighting in the teritory of Polres Grobogan jurisdiction. This research was conducted by applied a qualitative approach to the case study type also supported by interviews, observations, and documentation studies as data collection techniques. The data that has been obtained are then validated through a triangulation process and analyzed through a step of reduction measures, presented and maked conclusions. After that, the data were analyzed with management theory, achievement motivation theory and SWOT analysis theory. The final results of this study found a series of symptoms in the form of achieving consistency of dialogical patrol, marked by the fulfillment of the standardization of patrol activities as measured by the Regulation of the Head of the National Police Security Guard Agency of the Republic of Indonesia Number 1 of 2017 concerning Patrols. This patrol is good enough effective if looked by the process, but have not shown optimal results on a larger scale. This is influenced by internal factors which is strengths and opportunities and external factors which is weaknesses and threats, so that several efforts are needed to optimize the dialogical patrol to achieve the planned results.